2023
DOI: 10.1021/acscatal.3c00872
|View full text |Cite
|
Sign up to set email alerts
|

Elucidation of Active Sites and Mechanistic Pathways of a Heteropolyacid/Cu-Metal–Organic Framework Catalyst for Selective Oxidation of 5-Hydroxymethylfurfural via Ex Situ X-ray Absorption Spectroscopy and In Situ Attenuated Total Reflection-Infrared Studies

Abstract: Chemoselective oxidation of 5-hydroxymethylfurfural (HMF) over nonnoble metals to produce a bioplastic monomer, 2,5-furandicarboxylic acid (FDCA), under alkaline-free conditions is challenging and worthy of investigation. HMF oxidation into FDCA involves the concurrent oxidation of primary alcohol and an aldehyde functional group into carboxylic groups, which therefore demand a bifunctional catalyst containing dual active sites and chemoselective oxidation of HMF. The present work demonstrated the formation of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 103 publications
(190 reference statements)
0
9
0
Order By: Relevance
“…In continuation of our recent computational studies on the catalytic activities exhibited by various metal active sites in porous metal organic framework and polyoxometalate composite materials (Cu-BTC_PMA) and thermally degraded MIL88B, 40,41 in this study, we investigated the enzymatic peroxidase properties of degraded MIL88B via quantum chemistry approaches. 42,43 Recently, we examined the thermal transformation of MIL88B MOF and its catalytic role in accelerating the conversion of CO 2 into acetic acid, in conjunction with molecular modelling.…”
Section: Resultsmentioning
confidence: 99%
“…In continuation of our recent computational studies on the catalytic activities exhibited by various metal active sites in porous metal organic framework and polyoxometalate composite materials (Cu-BTC_PMA) and thermally degraded MIL88B, 40,41 in this study, we investigated the enzymatic peroxidase properties of degraded MIL88B via quantum chemistry approaches. 42,43 Recently, we examined the thermal transformation of MIL88B MOF and its catalytic role in accelerating the conversion of CO 2 into acetic acid, in conjunction with molecular modelling.…”
Section: Resultsmentioning
confidence: 99%
“…[7,80] In a recent investigation, a composite catalyst comprising a Cu-containing metal-organic framework (CuÀ MOF) and a polyoxometalate (CuÀ BTC_PMA) was examined for the base-free selective oxidation of HMF to FDCA (entry 9). [81] Even though a high oxygen pressure (20 bar) was used during this reaction, the excellent catalytic performance along with the unique catalytic structure that eliminates the need for noble metals, presents an intriguing avenue for future developments in environmentally friendly catalysts for HMF oxidation.…”
Section: Catalytic Performance For Base-free Oxidation Of Hmf To Fdcamentioning
confidence: 99%
“…Polyoxometalates (POMs) are a type of metal oxide cluster (typically W 6+ , Mo 6+ , Nb 5+ and V 5+ ) with unique structures and properties, including acidity, basicity, redox and photochemical properties. POMs have the well-defined structures and distinct sizes; therefore, they represent ideal systems for understanding the role of solid state metal oxides in catalysis. , Especially, lacunary POMs as inorganic multidentate ligands can stabilize effectively Ru single-atom, atomically precise Ag nanoclusters, and Pt, Au nanoparticles, etc., which act as catalysts exhibiting great application potential in catalytic hydrogenation, oxidation and carbon dioxide conversion. Notably, it has been demonstrated that oxygen vacancies could form as one of the important defects in metal oxide clusters, which played a crucial role in the catalytic reactions, as revealed by both theoretical calculations and experimental observations. In this scenario, oxygen vacancies in POMs can facilitate oxygen activation and boost the oxidation of various intermediate in oxidation of 5-hydroxymethylfurfural . On the other aspect, the oxygen vacancies in reduced polyoxovanadate-alkoxide can mediate the catalytic deoxygenation of styrene oxide to styrene .…”
Section: Introductionmentioning
confidence: 99%